2016
DOI: 10.1021/acs.iecr.6b02021
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Growth Mechanisms of Sodium Chlorate Crystals from Aqueous Solutions

Abstract: Difficulties in determining the crystal growth mechanism from growth rate versus solution supersaturation dependence are discussed. Obtained results indicate that in the supersaturation range of 0.66−1.56%, sodium chlorate crystals grow in accordance with the spiral growth model. It is shown that in the supersaturation range of 0.44−1.32%, the growth mechanism depends on crystal growth history. Namely, the exponent n in the power law R = Kσ n depends on the manner of supersaturation changes (varied from 1.3 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…It is shown that in the same experimental conditions, individual {100} sodium chlorate crystal faces grew at different rates. 9 Many crystal faces did not grow at all, which confirms the occurred stability of non-growing crystal faces at relatively high solution undercooling (to 13 °C). 27 The existence of zero growth rates probably depended on the proximity of solution supersaturation to critical supersaturation, which determined the dead zone width.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…It is shown that in the same experimental conditions, individual {100} sodium chlorate crystal faces grew at different rates. 9 Many crystal faces did not grow at all, which confirms the occurred stability of non-growing crystal faces at relatively high solution undercooling (to 13 °C). 27 The existence of zero growth rates probably depended on the proximity of solution supersaturation to critical supersaturation, which determined the dead zone width.…”
Section: Discussionmentioning
confidence: 90%
“…Histograms representing changes in GRD of sodium chlorate {100} faces in the experiments with the temperature increasing from 28.0 to 30.0 °C and with the temperature decreasing from 30.0 to 28.0 °C were published earlier. 9 …”
Section: Experimental Resultsmentioning
confidence: 99%
See 3 more Smart Citations